European Concerted Action on Anticoagulation - Poller, L.; Keown, M.; Chauhan, N.; van den Besselaar, A.M.H.P.; Tripodi, A.; Shiach, C.; Jespersen, J.; Conard, J.; Dias, D.; Egberg, N.; Iriarte, J.A.; Kontopoulou-Griva, I.; Otridge, B. (Thrombosis and Haemostasis, 2002)
A procedure for using citrated fresh plasmas for International Sensitivity Index (ISI) calibration of two types of whole blood point-of-care test (POCT) prothrombin time (PT) monitor systems has been assessed in a multicentre study.The CoaguChek Mini and TAS PT-NC systems gave higher ISI with whole blood samples than with fresh plasma calibrations. However, there was good agreement between whole blood and fresh plasma monitor system International Normalised Ratio (INR) and the reference INR of target samples.Reliable INR can therefore be obtained with both whole blood and plasma samples on these two POCT systems based on their respective ISI. With the CoaguChek Mini system, the plasma calibration ISI can also be used to derive reliable INR with whole blood PT results. This was not possible with the TAS PT-NC system.
Keywords: Prothrombin time; International Normalised Ratio; plasma calibrations; Multicentre ISI; POCT monitors